ANALISIS PENGARUH MUTU PELAYANAN KESEHATAN RUJUKAN PADA PROGRAM KJSU-KIA (KANKER, JANTUNG PEMBULUH DARAH, STROKE, URONEFROLOGI, KESEHATAN IBU & ANAK) TERHADAP KEPUASAN PASIEN DI RSUD.SAWERIGADING MENGGUNAKAN METODE STRUCTURAL EQUATION MODELING (SEM) - Rismayanti Amran; Rozalina AMRAN; Saparuddin Latu; Asnani; Julia Fitrianingsih; Muhammad Tahir Malik (LPPM Universitas Awal Bros, 2026)
This study aims to analyze the effect of referral healthcare service quality in the KJSU-KIA program (Cancer, Cardiovascular Disease, Stroke, Uronephrology, Maternal and Child Health) on patient satisfaction at Sawerigading Regional General Hospital (RSUD Sawerigading Palopo) using the Structural Equation Modeling (SEM) approach. Strengthening referral healthcare services has become one of the national health transformation priorities in Indonesia to improve access, quality, and continuity of healthcare services, particularly for catastrophic and priority diseases. This research employed a quantitative explanatory design with a cross-sectional approach involving 200 patients receiving KJSU-KIA referral services. Data were collected using SERVQUAL-based questionnaires covering five dimensions of service quality: Tangibles, reliability, responsiveness, assurance, and Empathy. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The findings revealed that reliability, responsiveness, and assurance had a significant positive effect on patient satisfaction, while Tangibles and Empathy did not show significant effects. Among all dimensions, responsiveness was identified as the most dominant factor influencing patient satisfaction. The structural model demonstrated strong explanatory power with an R² value of 0.618, indicating that service quality dimensions explained 61.8% of the variance in patient satisfaction. The study concludes that improving responsiveness, reliability, and professional assurance is essential to enhance patient satisfaction in referral healthcare services within the KJSU-KIA program at RSUD Sawerigading Palopo.